Fatores preditivos para o risco de disfunção sexual em mulheres climatéricas: estudo de base populacional - Reis, Sandra Cristina Romano Marquez (2019)
This study aimed to identify predictive factors for the risk of sexual dysfunction in climacteric women. It is a cross-seccional population-based study accomplished by household. The investigated parameters were sociodemographic characteristics, depressive simptomes (CES-D), level of physical activity (IPAQ), risk of sexual dysfunction (QS-F), self-rated health and satisfaction with sleep (extracted from WHOQOL bref). A hierarchical logistic regression was conduted into three blocks with significance of 5%. A total of 381 sexually active climacteric women participated in the study with a mean age of 55.04 (± 7.21) years. Schooling 8.49 (± 4.93) years; 82.7% claimed to have a partner and 72.17% reported insufficient income. As for the self-rated health 34.38% are dissatisfied, 26% are unsatisfied with their sleep and 26% were classified with depressive simptomes. As for the level of physical activity (IPAQ), 16.3% were considered active. The prevalence of risk for sexual dysfunction was 38.3%. All variables investigated were associated with risk for sexual dysfunction (P < 0.05). In the final model, the predictors of risk of sexual dysfunction were low satisfaction with sleep (OR⹀4.20; IC95% 2.32-7.62), old age (OR⹀1.04; IC95% 1.00-1.08), low schooling (OR⹀0.90; IC95% 0.85-0.970) and having a partner (OR⹀0.353; IC95% 0.163-0.76). These aspects are worthy of attention from the healthcare team, in order to prevent and early identify the risk of sexual dysfunction in menopausal women.